In vivo infection of sheep by bovine leukemia virus mutants. - Willems, L (1993)
Direct inoculation of a cloned bovine leukemia virus (BLV) provirus into sheep has allowed study of the viral infectivity of genetic mutants in vivo. Three BLV variants cloned from BLV-induced tumors and 12 in vitro-modified proviruses were isolated and analyzed for viral expression in cell culture. The proviruses were then inoculated into sheep in order to assess viral infectivity in vivo. Of three variants cloned from BLV-induced tumors (344, 395, and 1345), one (344) was found infectious in vivo. This particular provirus was used to engineer 12 BLV mutants. A hybrid between the 5' region of the complete but noninfectious provirus 395 and the 3' end of mutant 344 was infectious in vivo, suggesting that the tax/rex sequences were altered in virus 395. As expected, several regions of the BLV genome appeared to be essential for viral infection: the protease, pol, and env genes. Even discrete modifications in the fusion peptide located at the NH2 end of the transmembrane gp30 glycoprotein destroyed the infectious potential. In contrast, mutations and deletions in the X3 region present between the env gene and the 3' tax/rex region did not interfere with viral infection in vivo. This region of unknown function could thus be used to introduce foreign sequences. A BLV recombinant carrying a ribozyme directed against the tax/rex sequences was still infectious in vivo. Cotransfection of two noninfectious mutants carrying deletions led to infection in two of four independent injections, the infectious virus being then a recombinant between the two deletants. The experimental approach described here should help to gain insight into essential mechanisms such as in vivo viral replication, cooperation between deletants for viral infectivity, and viral superinfections. The gene products in the X3 and X4 region which are dispensable for in vivo infection could be involved in leukemogenesis, and thus proviruses deleted in these sequences could constitute the basis for a live attenuated vaccine.